Risk factors of heavy uterine bleeding in patients with endometriosis and adenomyosis treated with dienogest - Hiroaki Takagi; Masahiro Takakura; Toshiyuki Sasagawa (Elsevier, 2023)
Objective: Dienogest (DNG), a fourth-generation progestin, reduces pain associated with endometriosis and uterine adenomyosis; however, it is associated with irregular uterine bleeding that can cause anemia and poor quality of life. We investigated risk factors for heavy bleeding following DNG administration. Materials and methods: We retrospectively investigated patients who received DNG for risk factors of heavy uterine bleeding, including clinical diagnosis, use of pretreatment gonadotropin-releasing hormone agonist, smoking, cancer antigen 125, and blood hormone levels. We additionally assessed the uterine area in patients with uterine adenomyosis, the major axis of the uterine body, the major axis of myometrial thickness, the site of tumor development, and the site of myoma development in patients with uterine fibroids. Results: Eighty Japanese patients were administered DNG. The median age was 41 (range: 24-51) years. The odds ratio (OR) for moderate-to-severe bleeding according to clinical diagnosis were 0.33 (P = 0.011) for endometrioma and 9.00 (P = 0.049) for uterine adenomyosis. Receiver operating characteristic curve analysis of the uterine area associated with uterine adenomyosis showed an area under the curve (AUC) of 0.909 between those with major and minor bleeding, with an optimal cut-off value of 7388.2 mm2. The uterine body major axis had an AUC of 0.946, with an optimal cut-off value of 78.3 mm. The major axis of myometrial thickness had an AUC of 0.855, with an optimal cut-off value of 46.8 mm. Conclusion: Patients with endometrioma treated with DNG were less likely to experience heavy uterine bleeding. Uterine bleeding in patients with uterine adenomyosis and adenomyosis associated with uterine fibroids should be closely monitored while administering DNG.